THE IMPACT OF ETHIC TOWARDS MACEDONIAN CONSUMERS - Karemani, Argjina; Thaci, Selvije; Ferati, Rametulla; Baftijari, Yzeiri (European Scientific Journal, ESJ, 2014)
In this paper the implementation of the Ethic of products and servicesthat exists in the Republic of Macedonia iz analyzed. Therefore, the researchconducted in this paper shows the products and services which are beenoffered in Macedonia and how they manage to adhere to standards based ontheoretical and empirical research. It is emphasized the need for companiesto focus on issues related to ethics and the application of this process toenterprises in the Republic of Macedonia (specifically Pollog Region). Toanalyze this effect, it is necessary to use the method of surveying withcustomers in the Republic of Macedonia. The analysis was based on 50customers on Pollog Region, which clearly ilustrates how ethical areproducts and services of these companies and how consumers fail todistinguish between ethical and unethical products. However, with dataprocessing, is concluded that consumers have a relatively good knowledgeon ethical products and services; hence, products and services that thecustomers consume in this region are much less and are based on ethicalstandards.